Calculation of the same Lorentz factor using the opposite approach - Wu Wang (AIP Advances)
This article extends the law of electromagnetic oscillation to form a theoretical system of spatial particles. According to this theory, the speed of light is variable and motion is absolute. The Lorentz factor can be calculated using an absolute inertial coordinate system that converts the absolute inertial coordinate system in space B to the movement coordinate system in space A. The generalized Lorentz transformation is a transformation of different spaces; its core is the ratio of the speed of light, and a new method is used to derive the mass‒energy equivalence and rewrite Newton’s law of universal gravitation.